Serologic survey of West Nile virus in horses from Central-West, Northeast and Southeast Brazil - Silva, Jaqueline Raymondi; Medeiros, Larissa Campos de; Reis, Vinicius Pinho dos; Chavez, Juliana Helena; Munhoz, Thiago Demarchi [UNESP]; Borges, Gustavo Puia; Brioschi Soares, Otavio Augusto; Coelho de Campos, Carlos Henrique; Machado, Rosangela Zacarias [UNESP]; Baldani, Cristiane Divan [UNESP]; Cristiny Rodrigues Silva, Maria Luana; Maia Faria, Joice Lara; et al. (Fundacão Oswaldo Cruz, 2013)
Since the emergence of West Nile virus (WNV) in North America in 1999, there have been several reports of WNV activity in Central and South American countries. To detect WNV in Brazil, we performed a serological survey of horses from different regions of Brazil using recombinant peptides from domain III of WNV. Positive samples were validated with the neutralisation test. Our results showed that of 79 ELISA-positive horses, nine expressed WNV-specific neutralising antibodies. Eight of the infected horses were from the state of Mato Grosso do Sul and one was from the state of Paraiba. Our results provide additional evidence for the emergence of WNV in Brazil and for its circulation in multiple regions of the country.
Keywords: West Nile virus; Flavivirus; Brazil